Lexical Cohesion and Semantic Relation in the English Texts - Dina Pratiwi, Putu (Humanis; Vol 22 No 3 (2018), 2018)
This study is entitled Lexical Cohesion and Semantic Relation in the English texts.  The  aims  of  this  study  are  identifying  the  types  of  lexical  cohesion  and analyzing the semantic relation  found in the texts. The data were taken   from   five texts  with  different   genres.   It contains aspects of life and consists of twelve pages. This study was library research which applied the documentation method  to  collect  the  data.  The data of this study were analyzed using the qualitative method.  The theory applied in this study is cohesion in English that explains the types of cohesion into two; lexical cohesion and grammatical cohesion and analyzing the semantic relation found in the text. The result of the analysis shows a lot of lexical cohesions found in the data such as reiteration. Reiteration consists of repetition, synonym and superordinate. Collocation can be explained by means of; Antonym, the same ordered series, and certain lexical sets. Semantic relation between lexical items in the text that makes the text cohesive was also found in this study .